Mental fatigue impairs soccer-specific decision-making skill. Issue 14 (17th July 2016) - Smith, Mitchell R.; Zeuwts, Linus; Lenoir, Matthieu; Hens, Nathalie; De Jong, Laura M. S.; Coutts, Aaron J.
ABSTRACT: This study aimed to investigate the impact of mental fatigue on soccer-specific decision-making. Twelve well-trained male soccer players performed a soccer-specific decision-making task on two occasions, separated by at least 72 h. The decision-making task was preceded in a randomised order by 30 min of the Stroop task (mental fatigue) or 30 min of reading from magazines (control). Subjective ratings of mental fatigue were measured before and after treatment, and mental effort (referring to treatment) and motivation (referring to the decision-making task) were measured after treatment. Performance on the soccer-specific decision-making task was assessed using response accuracy and time. Visual search behaviour was also assessed throughout the decision-making task. Subjective ratings of mental fatigue and effort were almost certainly higher following the Stroop task compared to the magazines. Motivation for the upcoming decision-making task was possibly higher following the Stroop task. Decision-making accuracy was very likely lower and response time likely higher in the mental fatigue condition. Mental fatigue had unclear effects on most visual search behaviour variables. The results suggest that mental fatigue impairs accuracy and speed of soccer-specific decision-making. These impairments are not likely related to changes in visual search behaviour.